THE EFFECT OF ENVIRONMENTAL CONCERN ON ECO FRIENDLY FASHION PRODUCT PURCHASE DECISION: THE MEDIATOR ROLE OF GREEN BRAND IMAGE - Septiarini, Eka; Irsyadi, Faiz; Mutiah, Ceha (ACCRUALS (Accounting Research Journal of Sutaatmadja), 2024)
Indonesia is now dealing with a variety of environmental issues. These challenges pose a hazard to ecosystems and the environment. Waste is Indonesia's major environmental challenge. Large amount of waste was accumulated, totaling 32 million tons, including textile waste. The cause of this phenomenon is the growth of fast fashion industry. The Indonesian apparel textile industry's export growth climbed by 56% (Kemenperin, 2021), although the market for environmentally friendly clothes fell in 2020 with a compound annual growth rate (CAGR) of -3.24% (Business Wire, 2020). 28% of Indonesian customers comprehend eco-friendly products. So it might be assumed that Indonesians lack comprehension of an environmentally friendly product. The purpose of this research is to broaden the understanding of green customers' purchasing decisions for eco-friendly fashion products by presenting and testing an integrated conceptual model that investigates the influence of consumers' personal environmental concern, green brand image, and its relationships. Using descriptive and associative quantitative methods, 371 respondents who live in Indonesia and had an experience purchase ecofriendly fashion product filled the questionnaire through google form. Data analysis using PLS software which consists of outer model and inner model. The outcome retrivied 72.4% of green brand image are influenced by environmental concern. The environmental concern influences green purchase decision by 24.2%. The green brand image influences green purchasing decisions by 38.7%. Green brand image positively mediated environmental awareness and green purchasing decisions by 28.2%.